Relationship Between Client Satisfaction, Service Quality and Client Perception Towards the Effectiveness of Client Consultation Services - Bujang, Romzan; Kasuma, Jati; Isnin, Nadrawina; Neging, Pressca; Nuraida Ali Hassan, Aimi; Caisar Darma, Dio; Kuleh, Yohanes (International Journal of Psychosocial Rehabilitation, 2020)
The satisfaction and perception level of bankruptcy through an interview or consultation session has become a major issue in delivering a quality service provided by the Malaysia Department of Insolvency (MdI). The purpose of this study is to examine the relationship between client satisfaction, service quality, and client perception towards the effectiveness of client consultation service in the Malaysia Department of Insolvency Kuching branch. The foundation of client satisfaction, service quality, client perception, and effectiveness was assessed using a validated questionnaire. The empirical results indicate that the most dominant determinants are client satisfaction and client perception. For service quality, it was found to be significant and strongly correlated with a positive relationship towards the effectiveness of client consultation services. The main contribution of this paper has provided empirical evidence about the relationship between client satisfaction, service quality, and client perception of the effectiveness of client consultation services. Areas for future research are briefly discussed in this current study.